Face paint : the story of makeup - Eldridge, Lisa (Abrams Image, 2015)
"Make-up, as we know it, has only been commercially available in the last 100 years, but applying decoration to the face and body may be one of the oldest global social practices. Lisa Eldridge, one of the world's foremost make-up artists--with a very large and loyal public following of her own--has written the first real history of the subject. Face Paint will explore the reasons behind make-up's use, the actual materials employed and manufactured through the ages, the icons that people emulate and how they achieved their effects, the impact on women's lives and the present and future of make-up from high profile practitioners artists to cosmetic breakthroughs. Along with the glamorous trappings, this is also about women's history and the ways in which we can understand their story through the prism of make-up."--Publisher's description